Pulp Fibroblast Cell Apoptosis After Application of Hema Dentine Bonding Material with Ethanol and Water Solvent - Ira Widjiastuti (Associacao Brasileira de Divulgacao Cientifica, 2019)
The most common main materials for dentin bonding for composite resin restoration is 2-hydroxyethyl methacrylate (HEMA). HEMA has beneficial physical and chemical properties, and stable, yet toxic. The addition of ethanol or water, may reduce the toxic effect of HEMA. Ethanol solvent has lower H-bonding capacity compared to water solvent, so it can bind less free radicals from the residual monomer. This study aimed to analyze apoptosis due to dentine bonding application with ethanol and water solvent. Fibroblast culture cells were obtained from extracted third molar, by means of tripsinasion method. The cells were divided into 4 groups as reached confluent: cell culture without treatment as control, cell culture with scaffold chitosan, cell culture with scaffold and polymerized dentin bonding with ethanol or water solvent. Apoptosis observation was conducted using immunohistochemistry method with ethidium bromide acridin orange staining, under fluorescent microscope with 40× magnification. There was a significant difference among groups (p=0.0001), yet no differences found between different solvent. Apoptosis rate in fibroblast cells culture exposed to HEMA bonding with ethanol solvent was 67%, while the cells exposed to HEMA bonding with water solvent was 44%. The effect of dentin bonding with ethanol solvent and water solvent towards apoptosis rate of pulp fibroblast cells is not different.